PUBLIC ASSET MANAGEMENT STRATEGY THROUGH GREEN SUKUK AND PUBLIC-PRIVATE PARTNERSHIP INTEGRATED FRAMEWORK - Rahma, Nayla Maulida Ellysia; Putra, Rehan Perdana; Akbar, Syahrir (Jurnal Manajemen dan Dinamika Bisnis (JMDB), 2025)
This research aims to analyze public asset management strategies through the framework of integrating green sukuk and public-private partnerships (PPPs). A qualitative approach is employed, with data collected through a literature review to gather information on the potential and challenges of implementing such policies. The data is then analyzed descriptively to outline the framework for the proposed strategy. The findings of this study indicate that the primary potential of integrating green sukuk and PPP lies in inclusive and sustainable funding sources, significant environmental and social benefits, and efficient risk management. On the other hand, challenges to be addressed include regulatory complexity, limitations in financial capacity and infrastructure, and fluctuating investor risk perceptions. The framework for integrating green sukuk and PPP in public asset management begins with project planning and fundraising, selection and agreement with business entities, asset implementation and maintenance, followed by evaluation, reporting, and contract renewal. These stages are realized through a policy practice plan based on a pilot project. Keywords: Public Asset, Management Strategy, Green Sukuk, Public-Private Partnership